Studying the relationship between a number of carcass traits and their regression on live weight in sheep - Abdullah Hameed Salim; Haneen Sattar Abbas (University of Thi-Qar Journal of agricultural research, 2022)
This study was conducted in Suq Al-Shuyoukh district, south of Thi Qar province, for the period from 5/11/2021 to 8/5/2022 on a sheep sample consisting of 49 local Iraqi sheep (Arabi ) from one of the private sector herds.The study included slaughtering sheep in a butcher's shop, recording the traits of the carcass and the weight of the thigh inside the shop, and then taking a sample of the thigh meat to study some of its chemical traits .Chemical tests were conducted on the meat sample in the laboratories of the Faculty of Agriculture and the Marshes of the University of Thi Qar, and the genetic material was extracted and genetic analysis was done in the laboratory of the Marsh Research Center at the University of Thi Qar. We reached the following results: The traits of hot carcass weight, carcass length, carcass diameter, and thigh weight showed a highly significant and positive correlation among them, while the rest of the traits differed in their correlations in terms of morality or in terms of being negative or positive. Through the results of the statistical analysis, it was found that the value of the regression coefficient for the characteristics of hot carcass weight, carcass length, thigh weight, dressing percentage, pH of meat, and muscle fiber diameter on the live weight of the animal was positive (except for the dressing percentage) and highly significant (P≤0.01).